Small, medium, large, extra-large : Office for Metropolitan Architecture, Rem Koolhaas, and Bruce Mau - Sigler, Jennifer; Werlemann, Hans; Office for Metropolitan Architecture (New York, NY : The Monacelli Press, 1998)
02